KCa3.1 Inhibition Switches the Astrocyte Phenotype during Astrogliosis Associated with Ischemic Stroke Via Endoplasmic Reticulum Stress and MAPK Signaling Pathways - Yu, Zhihua; Yi, Mengni; Wei, Tianjiao; Gao, Xiaoling; Chen, Hongzhuan (Frontiers in Cellular Neuroscience, 2017)
Ischemic stroke is a devastating neurological disease that can initiate a phenotype switch in astrocytes. Reactive astrogliosis is a significant pathological feature of ischemic stroke and is accompanied by changes in gene expression, hypertrophied processes and proliferation. The intermediate-conductance Ca2+-activated potassium channel KCa3.1 has been shown to contribute to astrogliosis-induced neuroinflammation in Alzheimer’s disease. We here present evidence, from both astrocytes subjected to oxygen–glucose deprivation (von Ruden, #3239) and from the brains of mice subjected to permanent middle cerebral artery occlusion (pMCAO), that KCa3.1 represents a valid pharmacological target for modulation of astrocyte phenotype during astrogliosis caused by ischemic stroke. In the primary cultured astrocytes, OGD led to increased expression of KCa3.1, which was associated with upregulation of the astrogliosis marker, glial fibrillary acidic protein (GFAP). Pharmacological blockade or genetic deletion of KCa3.1 suppressed OGD-induced up-regulation of GFAP, endoplasmic reticulum (ER) stress marker GRP78 and phosphorylated eIF-2α through the c-Jun/JNK and ERK1/2 signaling pathways. We next investigated the effect of genetic deletion of KCa3.1 in the pMCAO mouse model. KCa3.1 deficiency also attenuated ER stress and astrogliosis through c-Jun/JNK and ERK1/2 signaling pathways following pMCAO in KCa3.1−/− mice. Our data suggest that blockade of KCa3.1 might represent a promising strategy for the treatment of ischemic stroke.